Pengaruh Profitabilitas, Leverage, Ukuran Perusahaan Terhadap Tax Avoidance Perusahaan Property dan Real Estate - Hermawan, Sakti; Sudradjat, Sudradjat; Amyar, Firdaus (Jurnal Ilmiah Akuntansi Kesatuan, 2021)
Financial statements are used by many parties to determine the condition of the company's financial performance. Financial statements are a very important source of information in assessing the company's performance and prospects for shareholders and the public as one of the bases in making investment decisions. The value of the information contained in financial statements can be affected by the timeliness of preparation and presentation of financial statements. Because of this, the timeliness of a company in compiling and presenting its financial statements is very important. The company's timeliness in preparing financial statements can be influenced by several things, both internal and external influences. This study was conducted with the aim of knowing whether Profitability, Leverage and Company Size have an influence on Tax Avoidance in Property and Real Estate companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2019 period. Previous research that has been done shows different results. Therefore, it is necessary to conduct another study with the aim of re- testing the theory of Tax Avoidance. The population of this research is 46 property and real estate companies. This study uses a purposive sampling method in taking samples, so that 31 sample companies are obtained for 3 years of observation (2017-2019) with 93 observations (observations). Research data obtained from sample companies which can be downloaded on the official website of the Indonesia Stock Exchange. This study uses descriptive statistical analysis and multiple linear regression analysis as data analysis techniques. The data analysis technique carried out first is descriptive statistical analysis, classical assumption test, multiple linear regression analysis and then hypothesis testing.